Q-Parameterization Control Method for a Class of Two Wheel Mobile Robot - Nawawi, S.W.; Sabikan, S.; Kanjou, O. (Journal of Advanced Research in Applied Mechanics, 2020)
This project presents an application of a robust controller based on the "QParameterization" theory to control the motion of the common and well known problem in control engineering the " Two-Wheeled Inverted Pendulum" (TWIP). This controller is applied to attain stability and good dynamic performance. The Qparameter is designed such that it characterizes the set of all stabilizing controllers for the " Two-Wheeled Inverted Pendulum" (TWIP) system. The selection and design of the Q-Parameter is based along the system behaviour constraining. The work is carried out in three stages. First, the derivation of the mathematical model for the " Two-Wheeled Inverted Pendulum" (TWIP) system. Second the design methodology of the proposed Q-Parameterization controller is presented. Finally a simulation process is carried out to evaluate the resulting controller and its performance. For comparison purposes an LQR controller are designed and the results were carried out.